Analisis Kinerja Pengelolaan Dana Desa Berdasarkan Value For Money di Desa Sitio-Tio Hilir Kabupaten Tapanuli Tengah - Tinambunan, Siti May Sarah; Ridwan, M.; Harahap, Rahmat Daim (LPPM Universitas Labuhanbatu, 2023)
The public sector is an important aspect of government in facing the economy in the future. Including the smallest category, namely village accounting as a public sector application that also needs to be considered. The public sector has demands to carry out accountability of public funds.Â In assessing the performance of the village government through the realization of the budget and expenditure reports can be a review for the village to realize good governance.Performance appraisal using value for money measurement, the author focuses on economic measurement, efficiency and effectiveness. The purpose of this study was to determine the management of village funds based on value for money in the village of Sitio-TioHilir,in assessing the financial performance of the government desaSitio-Tio Hilir Central Tapanuli.The method used is qualitative descriptive, from the results of research using value for money measurement it can be concluded that the financial performance of the village government is not optimal and continues to strive to improve its performance. In terms of economy for three years from 2019-2021is in the economic category.In terms of efficiency, 2019-2020 is inefficient, but 2019 and 2021 are efficient. In terms of effectiveness, 2019 and 2020 were quite effective, while 2018 was effective.